EL SIGNO IDEOLÓGICO EN EL DISCURSO HISTORIOGRÁFICO: EL CASO DE LA STORIA DELLA LETTERATURA SPAGNOLA (1941) DE CARLO BOSELLI Y CESCO VIAN: THE IDEOLOGICAL SIGN IN HISTORIOGRAPHICAL DISCOURSE: THE CASE OF CARLO BOSELLI AND CESCO VIAN’S STORIA DELLA LETTERATURA SPAGNOLA (1941) - ROCA BLAYA, Alberto (Signa: Revista de la Asociación Española de Semiótica, 2024)
Este artículo se propone como un análisis del componente ideológico en la construcción de la Storia della letteratura spagnola de Carlo Boselli y Cesco Vian, vinculada al imaginario fascista, publicada por primera vez en 1941; más concretamente, de la forma en que la ideología se convierte en el criterio rector de la selección y la valoración de los autores contemplados en este manual. Al vincularse tan claramente con una ideología, la capacidad performativa de la Storia queda estrechamente ligada a la suerte de un movimiento político. Al perder este su hegemonía, se desmorona la realidad que la narración de Boselli y Vian construye. Abstract: This article proposes an analysis of the ideological component in the construction of Carlo Boselli and Cesco Vian’s Storia della letteratura spagnola, linked to the fascist imaginary, first published in 1941; more specifically, of the way in which ideology becomes the guiding criterion for the selection and evaluation of the authors covered in this handbook. By linking itself so clearly to an ideology, the performative capacity of the Storia is closely tied to the fate of a political movement. As the latter loses its hegemony, the reality that Boselli and Vian’s narrative constructs falls apart. Keywords: Storia della letteratura spagnola. Ideology. Literary Historiography. History of Literature. Hispanism.